First fossil of the Giant Armored Catfish Acanthicus (Siluriformes, Loricariidae) from the Late Miocene of Entre Ríos Province, Argentina - Bogan, Sergio; Agnolin, Federico L. (Zootaxa, 2020)
Loricariidae is a very diverse lineage of Neotropical fishes, being the most speciose family of the order Siluriformes. However, the loricariid fossil record is still very sparse. The aim of the present contribution is to describe in detail several bones belonging to the loricariid genus Acanthicus coming from late Miocene beds located at the Paraná River cliffs, Entre Ríos province, Argentina. Fishes of the Acanthicus clade are currently restricted to the northern half of South America, being mainly distributed in the Orinoco and Amazonas basins, with a single genus reaching the Paraná-Plata basin. Acanthicus adds to the list of several taxa that are shared by the Miocene of Paraná, Amazonas and Orinoco basins, but that nowadays are absent in the former (e.g., Colossoma, Phractocephalus, and Brachyplatystoma), and are typical of large river channels. This report of Acanthicus supports a close affinity between freshwater faunas of the Paraná, Orinoco, and Amazonas basins. Miocene fossils of freshwater fishes recorded in Paraná beds shed light on the connections between ancient basins of South America and also indicate that several fish clades suffered regional extinctions during the late Neogene or the beginning of the Quaternary.